Application of Nanobioinformatics in Medical Science - A Probable Therapy - Dave, Kirtan; Mckechnie, Lawrence; Panchal, Hetal (Current Bioinformatics, 2011)
Nanotechnology and Bioinformatics are quickly evolving into a research field that encompasses the use of all kinds of biomedical information, from genetic and proteomic data to image data associated with a particular disease condition of a patient. Nanobioinformatics comprises the fields of nanotechnology (e.g., nanobiological particle, Nanomedicine) and Bioinformatics (e.g., genomics and proteomics) and deals with issues related to the approach of understanding the complex biological system and disease network in medicine, the analysis of high throughput genomics data, Nanobiology and computer added drug design, interoperability and integration of data-intensive biomedical applications. This review depicts some new requirements such as the development of new tools and technologies that are critical for the design, modeling, simulation and visualization of Nanosystems that have arisen during the accelerated evolution of Nanobioinformatics applied to medical science. The knowledge obtained at nanoscale implies the answer of new questions and the development of new concepts in different fields. The implementation of new tools and methods in medical science will be a key element to derive the information needed in order to unleash the promise behind this convergent field. This work will shed light upon some applications of Nanoinformatics in medical science, and will discuss how physical, chemical, and biological properties of nanoparticle are fulfilling the new requirements for different scientific fields such as Bioinformatics and Nanotechnology
Keywords: Bioinformatics